Chemical Composition and Safety of Unrecorded Grain Alcohol (Bai Jiu) Samples from Three Provinces in China - Newman, Ian M. (Int J Environ Res Public Health, 2018)
About 20% of spirits consumed in China are “unrecorded”, where these spirits are produced in small-scale distilleries and sold outside the systems of taxation and quality control. Researchers visited small distilleries in rural Yunnan, Hubei and Anhui and purchased 56 samples of unrecorded bai jiu. Seven samples of the recorded bai jiu were purchased as reference samples. An independent laboratory conducted a blind analysis of the samples. Results were compared to the standards for unrecorded alcohol adopted by the European Commission’s Alcohol Measures for Public Health Research Alliance (AMPHORA). No samples exceeded the AMPHORA guidelines for methanol, ethyl acetate, lead and cadmium; one sample exceeded 1000 g/hL of combined higher alcohols; one sample exceeded 100 mg/L of arsenic; and three samples exceeded 50g/hL of acetaldehyde, but only by relatively small amounts. Low-priced unrecorded bai jiu averaged 9.8 RMB/jin (500 mL), compared to 10.7 RMB/jin for inexpensive recorded bai jiu. The low-priced unrecorded bai jiu samples had a mean alcohol-by-volume of 51.8%, compared to 50.1% for the recorded bai jiu samples. The results did not raise any critical safety issues with unrecorded bai jiu, but there may be long-term health risks related to ethanol, acetaldehyde and arsenic. The social ties between the bai jiu makers and the people who consume their product are a deterrent to adulteration; but when bai jiu is sold outside of the social circle, the deterrent disappears.